2019
DOI: 10.3892/etm.2019.7675
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑889‑3p targets FGFR2 to inhibit cervical cancer cell viability and invasion

Abstract: MicroRNAs (miRNAs) are frequently dysregulated in cervical cancer, and the aberrant regulation of miRNAs may be involved in the regulation of various cancer-associated biological processes. Therefore, further exploration of the specific roles of dysregulated miRNAs in cervical cancer and their associated mechanism may promote the development of effective therapeutic approaches. miRNA-889-3p (miR-889) serves crucial roles in esophageal squamous cell carcinoma and hepatocellular carcinoma. However, to the best o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…41,42 Functionally, FGFR2 is believed to serve as an oncogene enhancing the malignant characteristics of cervical cancer. 43 Here, our results confirmed that ZFPM2-AS1 can positively regulate FGFR2 expression by functioning as a ceRNA of miR-511-3p in cervical cancer, thereby pointing to possible diagnostics and therapeutics based on the ZFPM2-AS1-miR-511-3p-FGFR2 axis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…41,42 Functionally, FGFR2 is believed to serve as an oncogene enhancing the malignant characteristics of cervical cancer. 43 Here, our results confirmed that ZFPM2-AS1 can positively regulate FGFR2 expression by functioning as a ceRNA of miR-511-3p in cervical cancer, thereby pointing to possible diagnostics and therapeutics based on the ZFPM2-AS1-miR-511-3p-FGFR2 axis.…”
Section: Discussionsupporting
confidence: 78%
“…To decipher the mechanism underlying the involvement of miR-511-3p in cervical cancer progression, we carried out bioinformatics analysis to find a downstream target of miR-511-3p. The 3′-UTR of FGFR2 mRNA was found to contain complementary binding sequences for the seed region of miR-511-3p ( Figure 5A), and FGFR2 was selected for further experimental verification because this gene is involved in the cervical carcinogenesis and cancer progression [41][42][43] in addition to being regulated by multiple miRNAs. [44][45][46] The luciferase reporter assay was performed to verify the above prediction.…”
Section: Fgfr2 Is a Direct Target Gene Of Mir-511-3p In Cervical Cancmentioning
confidence: 99%
“…14 Sun et al demonstrated that miR-889-3p reduced CC cell growth and invasion via targeting fibroblast growth factor receptor 2. 15 However, the expression and underlying roles of miR-3150b-3p in CC remain elusive. We suggested that miR-3150b-3p may serve as a tumor suppressor in CC.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small short‐strand non‐coding endogenous conserved single‐stranded molecule RNAs with a length of 18–25 nucleotides, which regulate gene expression by inhibiting specific sites in the 3 untranslated region of its target genes 8,9 . miRNA is widely found in eukaryotes and usually has a length of 18–25 nucleotides, and the 3' end can vary from 2 to 3 nucleotides, with varying lengths 10 .…”
Section: Introductionmentioning
confidence: 99%